Drosophila Patj plays a supporting role in apical-basal polarity but is essential for viability. - Zhou, W.; Hong, Y. (Development, 2012)
Patj has been characterized as one of the so-called polarity proteins that play essential and conserved roles in regulating cell polarity in many different cell types. Studies of Drosophila and mammalian cells suggest that Patj is required for the apical polarity protein complex Crumbs-Stardust (Pals1 or Mpp5 in mammalian cells) to establish apical-basal polarity. However, owing to the lack of suitable genetic mutants, the exact in vivo function of Patj in regulating apical-basal polarity and development remains to be elucidated. Here, we generated molecularly defined null mutants of Drosophila Patj (dPatj). Our data show conclusively that dPatj only plays supporting and non-essential roles in regulating apical-basal polarity, although such a supporting role may become crucial in cells such as photoreceptors that undergo complex cellular morphogenesis. In addition, our results confirm that dPatj possesses an as yet unidentified function that is essential for pupal development.